Chapter 5 The Recognition Paradigm Between Universalism and Historicism - Honneth, Axel (Taylor & Francis, 2022)
This chapter will, first, reconstructs Axel Honneth's account of the significance of recognition in his book The Struggle for Recognition and track some of the unresolved tensions in it and their role in Honneth's subsequent work. The final part of the chapter focusses on Honneth's more recent monograph The Freedom's Right, in which an oscillation of his position between universalism and historicism or relativism pauses in the latter end. This limits the applicability of the theory outside the confines of Europe or the West. It turns out that the reconstruction and immanent critique of Honneth's work, however, supports recognition-theoretical universalism.